FEATURES OF FUNCTIONAL READINESS OF CHILDREN TO SCHOOL - Gozak, Svitlana V.; Fіlonenko, Olga O. (Educological discourse, 2015)
We studied a «school maturity» to the systematic education at school by Kern-Ipasek, Wenger, Ozeretskii methods among senior pre-school age children in 3 children’s educational institutions. As a result of investigations we revealed that a significant part of the children functionally were not ready for education at school. Only 62.5 % of the children (56.8 % of boys and 68.1 % of girls) had a sufficient level of motivation preparedness within three months before beginning of education at school; 47.0 % of pre-school age children (25.6 % of boys and 68.3 % of girls) had a sufficient development of small motility by the indices of kinetic tremor; only 22.5 % of the children – by the indices of motormetric test.